Myanmar Country Environmental Analysis : Fisheries Sector Report - Fodor, Martin; Ling, Stephen (World Bank, Washington, DC, 2019)
Fisheries and aquaculture make a significant contribution to Myanmar's economy. The fisheries sector contributes roughly 2 percent of Myanmar's gross domestic product (GDP), 50 percent of animal protein consumption, 6 percent of employment—rising to as high as 34 percent in some coastal areas—and up to 56 percent of state/regional government revenue. Marine fisheries, freshwater fisheries, and aquaculture contribute to production in roughly equal proportions, for a total annual production of 3 million tons. Fisheries' contributions to economic output and employment in Myanmar still lag behind other countries in the region. For instance, the aquaculture sector alone contributes more to the GDP of Bangladesh and Vietnam (at more than 3 percent and more than 5 percent, respectively) than the entire fisheries sector's contribution to GDP in Myanmar. There is a scarcity of scientific data on which to base the management of Myanmar's fisheries. Official catch estimates show an inexorable rise in marine fisheries' production, but these are contradicted by stock assessment data suggesting that between 1979 and 2013 pelagic stocks fell by as much as 90 percent and demersal stocks by around 50 percent.